Management of endodontic-periodontic lesion of a maxillary lateral incisor with palatoradicular groove - Jayshree Ramakrishna Vishwas; Shoeb Yakub Shaikh; Varsha H. Tambe; Fareedi Mukram Ali; Mohammed Mustafa (Wolters Kluwer Medknow Publications, 2014)
Presence of palatal radicular grooves are considered to be an important contributing factor to the development of localized periodontitis, as it favored the accumulation and proliferation of bacterial plaque deep into the periodontium. Pulp involvement could result due to the introduction of bacterial toxins through channels that existed between the root canal system and the groove. Early diagnosis, elimination of inflammation and correction of anatomic complications are the key to a favorable outcome for managing palatoradicular groove. Present report describes successful management with an interdisciplinary approach of maxillary lateral incisor with combined endodontic periodontic lesion associated with palatoradicular groove.